2020
DOI: 10.3389/fphys.2020.00761
|View full text |Cite
|
Sign up to set email alerts
|

The Broad Spectrum of LMNA Cardiac Diseases: From Molecular Mechanisms to Clinical Phenotype

Abstract: Mutations of Lamin A/C gene (LMNA) cause laminopathies, a group of disorders associated with a wide spectrum of clinically distinct phenotypes, affecting different tissues and organs. Heart involvement is frequent and leads to cardiolaminopathy LMNA-dependent cardiomyopathy (LMNA-CMP), a form of dilated cardiomyopathy (DCM) typically associated with conduction disorders and arrhythmias, that can manifest either as an isolated event or as part of a multisystem phenotype. Despite the recent clinical and molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
77
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(94 citation statements)
references
References 101 publications
(150 reference statements)
0
77
0
Order By: Relevance
“…In addition, aortic valve morphogenesis arises at embryonic day (E)9.5, and the mature valves with fine defined leaflets are shaped at about E16.5 in mouse embryos, 16 while Lamin A/C start to be expressed in mouse extra-embryonic tissues around E8-9 and in the embryo around E10-12, playing an important role in cell differentiation, lineage specification, and tissue development. 2 Furthermore, the proper remodeling of aortic valves depends on multiple molecular pathways, especially Notch signaling. Recently, Lamin A has been reported to closely interact with Notch signaling and affect cell differentiation, even in cells of close developmental origin, such as cardiac mesenchymal cells and valve interstitial cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, aortic valve morphogenesis arises at embryonic day (E)9.5, and the mature valves with fine defined leaflets are shaped at about E16.5 in mouse embryos, 16 while Lamin A/C start to be expressed in mouse extra-embryonic tissues around E8-9 and in the embryo around E10-12, playing an important role in cell differentiation, lineage specification, and tissue development. 2 Furthermore, the proper remodeling of aortic valves depends on multiple molecular pathways, especially Notch signaling. Recently, Lamin A has been reported to closely interact with Notch signaling and affect cell differentiation, even in cells of close developmental origin, such as cardiac mesenchymal cells and valve interstitial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Pasotti et al reported that the cumulative event‐free survival was only 60% at 5‐years after LMNA ‐CMP diagnosis, and 45% of the events were sudden cardiac death or aborted sudden cardiac death 8 . However, only half of the patients with LMNA mutations had left ventricular dysfunction at the first visit, 9 owing to the age‐dependent penetrance of LMNA ‐CMP with development after the second decade of life in the majority of carriers and complete penetrance at 60 years of age 2 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lamin A/C are classified as intermediate filament proteins, the main constituent of the nuclear envelope with a structural role in the nucleus and the ability to regulate gene transcription through either direct or indirect modulation of chromatin organization, DNA replication, and signal transduction pathways [ 49 ]. In comparison to TTN variants, LMNA mutations most commonly result in brady- and tachy-arrhythmias together with cardiomyopathy, with a resulting high risk of sudden cardiac death often requiring pacemaker and/or defibrillator implantations [ 45 , 50 ].…”
Section: Dilated Cardiomyopathymentioning
confidence: 99%